2020
DOI: 10.1029/2020gl088280
|View full text |Cite
|
Sign up to set email alerts
|

Overpressured Underthrust Sediment in the Nankai Trough Forearc Inferred From Transdimensional Inversion of High‐Frequency Teleseismic Waveforms

Abstract: Active‐source seismic surveys have resolved the fine‐scale P‐wave velocity (Vp) of the subsurface structure in subduction forearcs. In contrast, the S‐wave velocity (Vs) structure is poorly resolved despite its usefulness in understanding rock properties. This study estimates Vp and Vs structures of the Nankai Trough forearc, by applying transdimensional inversion to high‐frequency teleseismic waveforms. As a result, a thin (∼1 km) low‐velocity zone (LVZ) is evident at ∼6 km depth beneath the sea level, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…This condition can be achieved when the λ value is the same as the λ b value for the given wedge geometry at the prism toe (Figure 6d). Because previous studies suggested that the prism toe area is unconsolidated and fluid can easily escape, the prism toe region is not considered to be overpressured (Akuhara et al., 2020; Screaton et al., 2009); therefore, λ = λ b = 0.5 is the likely pore pressure condition at the prism toe. Of our three candidate samples from C0006, C0006E‐36X‐1 with a μ w value of 0.57 would be the most representative for the prism toe because its clay mineral content of 40.9% may be reasonable to represent the Nankai sediment near the trench, which possibly contains detrital‐origin sediment in addition to hemipelagic sediment.…”
Section: Discussionmentioning
confidence: 99%
“…This condition can be achieved when the λ value is the same as the λ b value for the given wedge geometry at the prism toe (Figure 6d). Because previous studies suggested that the prism toe area is unconsolidated and fluid can easily escape, the prism toe region is not considered to be overpressured (Akuhara et al., 2020; Screaton et al., 2009); therefore, λ = λ b = 0.5 is the likely pore pressure condition at the prism toe. Of our three candidate samples from C0006, C0006E‐36X‐1 with a μ w value of 0.57 would be the most representative for the prism toe because its clay mineral content of 40.9% may be reasonable to represent the Nankai sediment near the trench, which possibly contains detrital‐origin sediment in addition to hemipelagic sediment.…”
Section: Discussionmentioning
confidence: 99%
“…For RF inversion, it can eliminate the subjective choice of the layer number. Many RF studies have used the RJMCMC algorithm for inverse problems in recent years Malinverno 2010, 2018;Akuhara et al 2020). Some of them have performed joint inversion with surface wave dispersion curves (Bodin et al 2012;Calò et al 2016), whereas detailed inversion settings differ among studies.…”
Section: Transdimensional Inversionmentioning
confidence: 99%
“…For the low frequency band, because the turning depth is close to the plate boundary, if seismic velocity discontinuities are present near the bottom of the prism, refracted and head waves can be generated. Indeed, the presence of a low velocity layer has been reported at the bottom of the accretionary prism in the southern DONET1 region (Park et al, 2010;Kamei et al, 2012;Akuhara et al, 2020). In this study, for the low frequency observations from DONET1, the retrieved P waves may contain such multiple P phases.…”
Section: Discussion P Wave Retrievalmentioning
confidence: 57%